Analysis of parenting patterns for mothers who have stunting toddlers - Usti Fina Hasanah Hasibuan; Siswanto Pabidang; Fatimah Sari (Science Midwifery, 2023)
Stunting is a condition in which children have a height below the standard according to age. This is caused by chronic malnutrition during the first 1,000 days of life, from pregnancy to 23 months of age. This research uses a type of qualitative research with a phenomenological approach, which is an approach that examines an object of research naturally or as it is. The results showed that early initiation of breastfeeding and exclusive breastfeeding was not applied to all toddlers. Some stunted toddlers are also not given exclusive breastfeeding, and the experience of informants in feeding children shows that children's appetite is reduced so that portions and frequency of eating are not as recommended. All informants provide complete basic immunization to their children, but only a few routinely weigh toddlers to the Posyandu every month. Regarding parenting, hygiene, and environmental hygiene, only one informant washed his hands using soap and running water before feeding the child.